Peningkatan Kesadaran Masyarakat terhadap Bencana Tsunami Melalui Media Video Edukasi bagi Masyarakat Pesisir Pantai Kunyit, Teluk Betung Selatan, Kota Bandar Lampung. : Peningkatan Kesadaran Masyarakat terhadap Bencana Tsunami Melalui Media Video Edukasi bagi Masyarakat Pesisir Pantai Kunyit, Teluk Betung Selatan, Kota Bandar Lampung. - Kholifatul Munawaroh; Regiana Revilia; Rara Gusnita Putri; Indah Grace Siani H; Intan Puspita Sari (Nemui Nyimah, 2026)
This community service aims to increase the knowledge and awareness of the residents of Pantai Kunyit, Bandar Lampung City, as active subjects in tsunami disaster mitigation efforts. This coastal area is highly vulnerable, yet it faces major challenges regarding low preparedness, lack of rapid response to early warnings, and an unsustainable mitigation culture. The implementation methods included short interviews for initial knowledge mapping, screening of interactive educational videos on tsunami mechanisms and self-rescue procedures, and quantitative evaluation using pre-test and post-test instruments. This initiative successfully engaged the active participation of residents, community leaders, and local government. The results demonstrated a significant increase in post-test scores compared to pre-test scores, indicating an enhanced public understanding of basic tsunami concepts, natural warning signs, and evacuation routes/shelters. Although community knowledge improved, fostering deeply rooted safety behaviors still requires consistent follow-up and commitment from various stakeholders, including the local government. This program is expected to serve as an initial catalyst to encourage multi-stakeholder collaboration towards creating a resilient and tsunami-prepared community in Pantai Kunyit.